Prácticas alimentarias y estado nutricional durante el embarazo en gestantes de la IPRESS I-2 Maynas e IPRESS I-4 Moronacocha, 2022 - Vasquez Rojas, Wendy Kiara (2024)
The objective of this research was to establish the relationship between dietary practices and the nutritional status of pregnant women attended at IPRESS I2 Maynas and IPRESS I-4 Moronacocha. The study was non-experimental, with a quantitative, descriptive, correlational and cross-sectional approach. The sample was selected by convenience, being 150 pregnant women for each IPRESS. A questionnaire on dietary practices during pregnancy and a nutritional evaluation form were used as data collection instruments. The results show that the highest percentage presented adequate practices, and a small percentage had inadequate practices in both health centers. On the other hand, a higher percentage had a normal nutritional status, and a lower percentage was overweight and obese. Likewise, the pregnant women presented a high weight gain, as well as the majority did not have anemia, and a normal uterine height in both IPRESS respectively. The study concluded that dietary practices are related to the nutritional status of pregnant women attended at IPRESS I-2 Maynas and IPRESS I-4 Moronacocha with a statistically significant p-value of 0.000.